Design builds business - Knowles, Andy (Henry Stewart Talks, 2010)
Commercial design as a business tool, The battle between consumer brands and private label, Shopper behaviour, Brand innovation, Brand renovation, Habitual shopping, The role for design in high interest categories, Gift packaging, The importance of brand naming, ROI or return on investment, Design effectiveness award winners